A Companion to the Abbey of Cluny in the Middle Ages
1 online resource.
Keywords: Founded in 910 by Duke William of Aquitaine, the abbey of Cluny rose to prominence in the eleventh century as the most influential and opulent center for monastic devotion in medieval Europe. While the twelfth century brought challenges, both internal and external, the Cluniacs showed remarkable adaptability in the changing religious climate of the high Middle Ages. Written by international experts representing a range of academic disciplines, the contributions to this volume examine the rich textual and material sources for Cluny's history, offering not only a thorough introduction to the distinctive character of Cluniac monasticism in the Middle Ages, but also the lineaments of a detailed research agenda for the next generation of historians. Contributors are: Isabelle Rosé, Steven Vanderputten, Marc Saurette, Denyse Riche, Susan Boynton, Anne Baud, Sébastien Barret, Robert Berkhofer III, Isabelle Cochelin, Michael Hänchen, Gert Melville, Eliana Magnani, Constance Bouchard, Benjamin Pohl, and Scott G. Bruce.